Method of determination of the leaf area of the potato cultivar Ágata from linear dimensions - Jadoski, Sidnei Osmar; Lopes, Édina Cristina; Maggi, Marcio Furlan; Suchoronczek, Adriano; Saito, Larissa Romão; Denega, Sergio (Semina: Ciências Agrárias, 2012)
The cultivar Ágata is currently the most widely cultivated in areas of potato production in Brazil, however, are necessaries basic information about its characteristics, especially on the development of the canopy. The work was developed in experimental area of the Unit of Research in Potato Culture and Microclimate for Agriculture, in the department of Agronomy of the UniversidadeEstadual do Centro Oeste (Unicentro), in Guarapuava (PR). The aim was to evaluate the efficiency of the adjustment of different mathematic models to determine the leaf area of potato plants of the cultivar Ágata. The evaluations were performed considering the dimensions of a 100 seeds of several sizes which were randomly collected in the phase of maximum vegetative development of plants. The data obtained were submitted to analysis of regression, being tested six different mathematic models: linear, quadratic, cubic functions and the exponential models from growth, Gauss and Lorentz, using the length and the height of leaves as independent variable to the adjustment in function of the real leaf area measured in laboratory. The variable length and the product of length x width of the leaf were those who presented the best results of adjustments to the models tested. With more emphasis to the length, for which all the models testes present statistical significance. It was concluded that the leaf length is the most appropriated parameter to be used in evaluation of the leaf area of potato plants cultivar Ágata, being the exponential function of growth and Lorentz the less recommended since its lowest adjustment coefficient.